ANALYSIS OF JOINT COST ALLOCATION IN DETERMINING COST OF GOODS PRODUCTION - Lawberto Sugiarto; Sri Handayani; Dheny Biantara; iwan Lesmana (Universitas Agung Podomoro, 2024)
This scientific research paper aims to provide a detailed understanding of joint cost analysis using the 4(four) methods: physical, sales value at split-off point, net realizable value and constant-gross matgin method. This is research aims to provide information for cake store X on how to manage the costs of production, and to improve the management strategies, for it is known that the store uses the simplest recording of accounting which records only the purchase of inventory while deducting it from the sales of finished goods to determine the profit for the year. The results from this research is the most effective joint cost allocation method for cake shop X is the physical method because it is easy to implement.